An efficient approach to approximate solutions of eighth-order boundary-value problems - İnç, Mustafa; Evans, DJ (Taylor & Francis Ltd, 2004)
In this paper, the approximate solutions to the eighth-order boundary-value differential equations are solved by using the Adomian decomposition method (ADM). The numerical solutions of the problem are calculated in the form of a series with easily computable components. The numerical illustrations show that this technique is more reliable, efficient and accurate than the traditional schemes.
Keywords: Adomian decomposition method; Adomian polynomials; the eighth-order differential equations